Adenosine Receptors Influence Hypertension in Dahl Salt-Sensitive Rats: Dependence on Receptor Subtype, Salt Diet, and Sex. Issue 2 (August 2018) - Jackson, Edwin K.; Gillespie, Delbert G.; Mi, Zaichuan; Cheng, Dongmei
Abstract : The influence of adenosine receptors on blood pressure in salt-sensitive hypertension is unknown. Here, we examined the effects of salt diets on arterial blood pressures (radiotelemetry) in female and male Dahl salt-sensitive wild-type versus female and male Dahl salt-sensitive A1, A2A, or A2B receptor knockouts (A1 KOs, A2A KOs, and A2B KOs, respectively). At baseline, all rats were on a 0.3% salt diet; then separate groups were switched to either 4% or 8% salt diet for 2 weeks. Compared with wild-types, baseline pressures were not affected by knockout of A1 or A2B receptors; yet, mean, systolic, and diastolic pressures were significantly ( P <0.01) higher in A2A KOs versus wild-types, an effect independent of sex. During the second week on a 4% salt diet, mean, systolic, and diastolic blood pressures (mm Hg, mean±SEM) in female A1 KOs (176±5, 209±5, and 147±4, respectively) and A2B KOs (166±8, 198±9, and 139±8, respectively) were significantly lower ( P <0.001) than wild-type on a 4% salt diet (202±4, 240±5, and 172±3, respectively). Male A1 KOs and A2B KOs were not protected against 4% salt diet–induced hypertension. This female advantage was overwhelmed by an 8% salt diet. Female and male A2A KOs were more salt sensitive, a phenotype that was apparent in male A2A KOs on 4% and 8% salt diets and in females on 8% salt diet. Female A1 KOs and A2B KOs were less susceptible to salt-induced stroke and experienced improved survival. Adenosine receptors influence blood pressure and survival in salt-sensitive rats, and the impact of deleting adenosine receptors on blood pressure and survival depends on salt diet and sex. Abstract : Supplemental Digital Content is available in the text.